UNVEILING TEACHER’S METACOGNITION IN PROMOTING EFL YOUNG LEARNERS’ CRITICAL THINKING IN INDONESIA - Rahmat Agung Azmi Putra; Sri Setyarini; Yanty Wirza (Edusentris, 2022)
The 21st-century education insists students to be ready to face global challenges with some skills, such as collaboration, creativity, critical thinking, and literacy. Despite a multitude of suggestions gained from several studies, the lack of understanding or compromise on the best approach to involve students’ thinking skills is a major concern. Therefore, this paper presents the research findings on teacher’s metacognition in promoting EFL young learners’ critical thinking skills. A case study was employed involving one class of fifth-grade students with one English teacher and three instruments to collect data namely classroom observation, interview with the teacher and document analysis. The collected data were analysed by referring to the theory of teachers’ metacognition and critical thinking skills. The findings reveal that the teacher applied three types of metacognitive knowledge, such as person, task, and strategies as identified from her metacognitive strategies, such as planning, monitoring, and evaluating the learning strategies. It is supported by the teacher’s statement who claimed that metacognition plays an important role to promote students ‘critical thinking because it guides herself through what, why, and how the students’ learning based on their needs and characteristics.